Massed treatment of posttraumatic stress disorder, traumatic brain injury, and co-occurring conditions: the Home Base intensive outpatient program for military veterans and service members - Harward, Laura K.; Lento, René M.; Teer, Andrew; Samph, Stephanie; Parmenter, Megan E.; Bonvie, Joseph; Magee, Charlotte; Brenner, Lauren; Picard, Kaitlin; Sanders, Wesley; Tinney, William Joseph; Andrew, Cyrielle; et al. (Frontiers in Psychiatry, 2024)
The two-week Home Base Intensive Clinical Program (ICP) provides treatment to veterans and active duty service members suffering from primary diagnoses of posttraumatic stress disorder (PTSD), traumatic brain injury (TBI), anxiety, or depression. First launched in 2015, this paper provides a programmatic update, including new treatment components implemented since inception, and examines outcomes for all participants who entered the program from September 2015 to July 2024 (n = 2561). The Home Base ICP provides a massed care approach through daily individual Prolonged Exposure, Cognitive Processing Therapy, Unified Protocol, or cognitive rehabilitation, along with groups targeting coping skills. Participants entering the program are provided with core group programming, as well as individualized therapy sessions tailored to their unique needs and symptom presentation. Supplemental dual recovery support is also available for all participants with co-occurring substance use or behavioral addiction concerns. Participants' support people receive education, support, and case management services. Participants have a multidisciplinary team comprising therapists, psychopharmacology providers, case managers, nurses, and wellness providers. Results demonstrate that program participants exhibited statistically significant reductions in PTSD symptoms (Cohen's d = 0.80), depression (d = 0.68), post-concussion symptoms (d = 0.71), and increased satisfaction in social roles (d = -0.65). Completion rate was 94.60% (n = 2422), suggesting that the Home Base ICP is a well-received and effective model of care for veterans and service members.